Plasminogen binding and degradation by Treponema denticola: Identification of the plasminogen binding interface on the FhbB protein. (23rd April 2018) - Tegels, B.K.; Oliver, L.D.; Miller, D.P.; Marconi, R.T.
Summary: Treponema denticola is a proteolytic‐anaerobic spirochete whose abundance in the subgingival crevice correlates with periodontal disease severity. Treponema denticola evades serum‐mediated killing through the binding of factor H (FH), a negative regulator of the complement system. The T. denticola FH receptor has been identified as FhbB, an 11.4kDa immunodominant lipoprotein. Three distinct subfamilies of FhbB proteins have been delineated and designated as FhbB1, FhbB2 and FhbB3. In this study we demonstrate that all FhbB variants bind human plasminogen (Plg). Competitive binding analyses revealed that FH and Plg do not compete for binding. Binding studies with FhbB135405 site‐directed amino acid substitution mutants demonstrated that the interaction domains for FH and Plg on FhbB are separable. Inhibition of Plg‐FhbB binding by ε‐aminocaproic acid (a lysine analog) indicates that binding is mediated by electrostatic interactions that presumably occur with Lys binding sites contained within Plg "Kringle" domains 1, 2, 4 or 5. Similar to that demonstrated for FH, Plg can also serve as a substrate for the T. denticola protease, dentilisin. The in vivo consequences of dentilisin‐mediated cleavage of Plg remained to be determined. The data presented demonstrate that FhbB is a multi‐functional protein that may contribute to virulence through several mechanisms including immune evasion, manipulation of the host immune response, adherence or tissue invasion.